Rectangular shell plating under uniformly distributed hydrostatic pressure - Neubert, M.; Sommer, A. (National Advisory Commitee for Aeronautics, 1940)
A check of the calculation methods used by Foppl and Henky for investigating the reliability of shell plating under hydrostatic pressure has proved that the formulas yield practical results within the elastic range of the material. Foppl's approximate calculation leaves one on the safe side. It further was found on the basis of the marked ductility of the shell plating under tensile stress that the strength is from 50 to 100 percent higher in the elastic range than expected by either method.
"December 1940."
NACA TM No. 965.
Translated from Luftfahrtforschung. Vol. 17, No. 7, pp. 207-210, July 20, 1940, by the National Advisory Commitee for Aeronautics.
Keywords: Shells (Engineering); Plates (Engineering); Hydrostatic pressure.; Strains and stresses.; Mathematics.; elektronické knihy; electronic books